INTERPRETATION OF SADAQAH VERSES AND HADITH IN AN ISLAMIC PERSPECTIVE - Riky Soleman (Program Studi Ekonomi Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
Alms is a form of sunnah practice that is highly recommended for Muslims. The practice of alms is highly recommended by Islam as evidence of concern for others. For those who give alms will be promised a reward by Allah SWT and those who receive alms will get ease in life. The results of this study state that the results of the interpretation of the Qur'an and Hadith, where the interpretation cannot be separated from the context of the times. The interpretation of the verses of the Qur'an and the hadith of the Prophet SAW, alms has a broader meaning than just helping others with money or goods. Alms also means that every Muslim carries out several practices that are directly related to social behavior and good deeds, both in the form of wealth, energy and thoughts. engage in several practices that are directly related to social behavior. For those who give alms will be promised a reward by Allah SWT and those who receive alms will get ease in life.